2021
DOI: 10.1093/carcin/bgab121
|View full text |Cite
|
Sign up to set email alerts
|

MiR-145 modulates the radiosensitivity of non-small cell lung cancer cells by suppression of TMOD3

Abstract: Radioresistance is a major problem encountered in the treatment of non-small cell lung cancer (NSCLC). Aberrant microRNA (miRNA) expression contributes to multiple cancer‑associated signaling pathways, and profoundly influences effects of radiotherapy (RT) in cancers. MicroRNA-145-5p (miR-145) is recognized as a tumor suppresser in NSCLC. However, the roles of miR-145 during radiotherapy of NSCLC are largely unknown. The present study aimed to investigate the function and underlying mechanism of miR-145 in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The SPSS 26.0 software was used for statistical analysis of the data involved in this study, and the measurement data were verified [ 24 ]. After confirming that the data were normally distributed, mean ± standard deviation (‾ x ± s ) was used to represent the data differences between groups, and a t -test was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The SPSS 26.0 software was used for statistical analysis of the data involved in this study, and the measurement data were verified [ 24 ]. After confirming that the data were normally distributed, mean ± standard deviation (‾ x ± s ) was used to represent the data differences between groups, and a t -test was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, functional experiments showed that miR-145-5p attenuated proliferation, migration and invasion in the Eca109 cell line. In fact, much evidence has revealed that miR-145-5p functioned as a tumor suppressor and that the expression levels of miR-145-5p were extremely downregulated in certain types of cancers to avoid antioncogenic functions ( 10 , 17 , 19 - 21 ). The results of our study also show that the miR-145-5p level is significantly associated with the progression of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the authors investigated the role of miR-145-5p in the regulation of ADP ribosylation factors 6 (ARF6) in the tumorigenesis of UTUC. MiR-145-5 p is a well-studied tumor suppressor microRNA, which is downregulated in many cancers [ 209 ] and it is related to poor prognosis in prostate, gastric, cervical, glioblastoma and non-small cell lung carcinoma (NSCLC) [ 210 , 211 , 212 , 213 , 214 ]. ADP-ribosylation factor 6 (ARF6), expressed widely in mammalian cells, is a small protein that is involved in several biological mechanisms, such as membrane trafficking and actin cytoskeletal rearrangement [ 215 ].…”
Section: Promising Microrna Biomarkers In Utucmentioning
confidence: 99%